Penggunaan Media Mikrofon Untuk Meningkatkan Kepercayaan Diri Dalam Pembelajaran Bahasa Indonesia Siswa Kelas 9 SMPN 1 Ngamprah - Emi Kulsum (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
The microphone is a supportive tool that can enhance students' confidence during classroom learning. As confidence increases, students can develop their potential more firmly, particularly in mastering speaking skills, understanding the material, and engaging with the audience. By using a microphone, their voices are more audible, articulation is clearer, and they can better control the forum. The method used in this research is a descriptive qualitative research method, employing an exploratory approach with Likert scale questionnaires and open-ended questionnaires, as well as documentation of responses through the Mentimeter application. The data recorded came from 55 participants out of a population of 104, distributed across three classes: 9A, 9B, and 9C. The results indicate that the microphone can enhance confidence in learning Indonesian, as evidenced by responses: Strongly Disagree 0.4%, Disagree 5.3%, Neutral 39%, Agree 41%, and Strongly Agree 14%. The open-ended questionnaire responses aligned with the students' progress in learning Indonesian. Therefore, the use of microphones should be consistently implemented in the learning process, especially in Indonesian language instruction.